Ethiopia's Tourism Sector : Strategic Paths to Competitiveness and Job Creation - World Bank (Washington, DC, 2013)
This study analyzes strategic intervention options that can inform the implementation process of Ethiopia s national tourism development policy in an effort to make the sector globally competitive. It also outlines the analytical foundations for technical assistance that will be provided to Ministry of Culture and Tourism (MoCT) by the World Bank-funded Ethiopian Sustainable Tourism Development Program (ESTDP). This study uses the world economic forum tourism and travel competitiveness index and International Finance Corporation (IFC) Doing Business report to benchmark Ethiopia s tourism competitiveness with respect to that of countries such Tanzania, Kenya, Egypt, and South Africa. It also draws lessons from and measures the tourism sector against other successful national economic sectors, such as floriculture. The focus of this study is on competitiveness at the value chain and destination levels. It identifies constraints affecting competitiveness and proposes strategic interventions that can help to address these challenges by taking advantage of existing opportunities. This study is mainly prepared for Ethiopia s tourism policymakers, particularly in MoCT. Secondary audiences include tourism-related ministries and public institutions, such as the Ministry of Trade and Investment, the Ministry of Education, the Ministry of Transport, the Ministry of Finance and Economic Development, the Ministry of Foreign Affairs and the Ministry of Communication and Information Technology, among others. Tourism sector stakeholders, in particular the private sector, as well as training institutions and donors are also targeted as readers. Having the national tourism policy as its main reference, this study focuses on short-term strategic interventions that can help to improve tourism competitiveness under the major pillars outlined in the policy. It also emphasizes growth and employment generation in line with current national targets and priorities as described in the Government of Ethiopia s national growth and transformation plan 2010-11 and 2014-15.